THE DEPICTION OF FEMALE SLAVES IN 2023 INDONESIAN NOVELS - Umaya, Nazla Maharani; Annisa, Zuraida Jihan; Harjito, Harjito; Septiana, Ika (Marwah: Jurnal Perempuan, Agama dan Jender, 2024)
This article describes the results of research on the depiction of female slaves in Indonesian novels published in 2023 and the assumptions on the basis of the existence of slavery in Indonesian novels in the 2023 era. Through novels, slavery can be remembered again and provide a lot of information. Books that tell stories about colonial events are not only books published several years after colonial events. The Indonesian novel published in 2023 also tells the story of slavery, and even clearly describes how and what female slaves experienced during the colonial period. The research was completed using library study methods and note-reading techniques. The results of data acquisition are described qualitatively. The results of the research found several depictions of female slaves during the colonial period in Indonesian novels published in 2023. Slavery and women is a record of historical events that depict the journey of an important period in Indonesia that should always be read throughout time, including until 2023.